William of Malmesbury and fortuna. Issue 1 (1st January 2018) - Forster, Tom Stephen
ABSTRACT: The great Benedictine historian William of Malmesbury has divided scholarly interpretation over recent decades. For some, William was a precocious scholarly talent who steered around or subverted the constraining absurdities of the providential orthodoxy. For others, his explicit expressions of faith in God's providence, despite its often vexatious reverses, betray a sincere piety and reverence for the hidden justice of divine cosmic rationality. These conclusions have relied on flawed assessments of William's use of the term fortuna, fortune. They adhere to a broader status quo that imagines all medieval thinkers took for granted that fortune's reverses were inscrutable and inevitable. On the contrary, this article argues that William was concerned with determining the precise causes of fortune, so that he might prescribe ethical advice to prevent its reverses. This has consequences for understanding the ends of twelfth-century historical writing and the development of thought pertaining to individual and collective punishments.